Decomposition method in solving multicommodity network flow problem - 494150 Norhuda Ikhsan; Sabariah Baharun; Fakulti Sains (2008)
Project Paper (Sarjana Muda Sains serta Pendidikan (Matematik)) - Universiti Teknologi Malaysia, 2008